2014
DOI: 10.1002/pro.2606
|View full text |Cite
|
Sign up to set email alerts
|

Protein unfolding rates correlate as strongly as folding rates with native structure

Abstract: Although the folding rates of proteins have been studied extensively, both experimentally and theoretically, and many native state topological parameters have been proposed to correlate with or predict these rates, unfolding rates have received much less attention. Moreover, unfolding rates have generally been thought either to not relate to native topology in the same manner as folding rates, perhaps depending on different topological parameters, or to be more difficult to predict. Using a dataset of 108 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 62 publications
(111 reference statements)
1
41
0
Order By: Relevance
“…Instead, they found that the refolding rate constant was highly dependent on relative contact order, a measure of local and non-local contacts in a protein's native structure. Broom et al (32) corroborated their result and showed that the unfolding rate constant also correlated with contact order, although less well. They concluded, "Unfolding rates correlate better with thermodynamic stability."…”
Section: Opening and Closing Kinetics That Expose The Buried Cys In Mmentioning
confidence: 94%
“…Instead, they found that the refolding rate constant was highly dependent on relative contact order, a measure of local and non-local contacts in a protein's native structure. Broom et al (32) corroborated their result and showed that the unfolding rate constant also correlated with contact order, although less well. They concluded, "Unfolding rates correlate better with thermodynamic stability."…”
Section: Opening and Closing Kinetics That Expose The Buried Cys In Mmentioning
confidence: 94%
“…ACO/LRO are measures of topological complexity based on the sequence separation of contacting residues in the folded protein. We have shown recently that the rates of protein folding and unfolding both decrease with increasing ACO/ LRO (41). LRO provides a more linear and stronger correlation and is normalized for increasing protein size, which also slows (un)folding (41,42).…”
Section: Modeling Reveals the Molecular Mechanisms For Threefoil's LImentioning
confidence: 97%
“…We have shown recently that the rates of protein folding and unfolding both decrease with increasing ACO/ LRO (41). LRO provides a more linear and stronger correlation and is normalized for increasing protein size, which also slows (un)folding (41,42). As ACO/LRO provide just a simple measure of protein structural complexity, we used Gō models to further define the molecular origins of ThreeFoil's high barrier.…”
Section: Modeling Reveals the Molecular Mechanisms For Threefoil's LImentioning
confidence: 99%
See 2 more Smart Citations